Pengaruh Inflasi, NPF, BOPO terhadap Total Aset Perbankan Syariah di Indonesia (Studi pada Bank Umum Syariah Periode 2013 – 2019) - Triana Puji Lestari; Musyafa' Musyafa' (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
This study to determine the effect of inflation, non-performing finance (NPF), operating expenses and operating income on the total assets of Islamic banking in Indonesia. The method used in this research is descriptive quantitative. Using secondary data sourced from the company website. The population of Islamic commercial banks for the period 2013-2019 with a sample size of 63. The results of this study are that inflation does not have a significant effect on the total assets of Islamic banking, non-performing finance (NPF) has no significant effect on total assets of Islamic banking and operating expenses operating income (BOPO). Sharia banking has a significant effect on total assets, but simultaneously inflation, non-performing finance (NPF), operating expenses (BOPO) have a significant effect on total assets of Islamic banking.